Public Engagement for Objective and Holistic Officials’ Evaluation: an Integrated Political-Social-Legal View - Anindyo Widhoyoko, Samuel; ., Sasmoko; Khan, Aqeel; Chariri, Anis (International Journal of Engineering and Technology, 2018)
This research proposes new model of officials’ evaluation grounded on a belief regarding to the urgency of a framework which embraces socio-political aspects holistically. This is derived from national vision in sustainability development demanding a more transparent, reliable, and competent leadership. Regarding to this, distortions often occur due to governance malpractices in the form of corruption which impact officials’ performance as well as environment conduciveness. This phenomenon is taken as a fundamental paradigm of this research which results in a reasoning stating that officials’ objective evaluation. This research realizes that cannot be done by considering officials as a single-role entity. It must consider several roles which impacts and influences several different parties (political, social, and governmental). This research comprehends such gap through comprehensive literature review and transforms all theories in the purpose of building a systematic assessment methodology which captures various aspects from different perspective. In its discussion, this model is proven academically to be able to evaluate officials’ performance objectively through three broad parameters: (1) policies formulation, (2) social engagement, and (3) regulatory submission. In addition, those three categorical assessment would be integrated in a weighted-average system, enabling them to produce a numerical score. In this stage, this framework is applied through information technology is used to capture data from different respondents.